2023
DOI: 10.3389/fphys.2023.1126057
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of the impact of combined taxane and carboplatin treatment on autonomic nerves in patients with cervical cancer: Measurement of heart rate variability

Abstract: Background: Previous studies have shown that heart rate variability (HRV) analysis is a sensitive indicator of chemotherapy-induced cardiotoxicity. However, most studies to date have observed long-term effects using long-term analyses. The main purpose of this study was to evaluate the acute effect of chemotherapy on the cardiac autonomic nervous system (ANS) in patients with cervical cancer (CC) by examining short-term HRV.Methods: Fifty patients with CC admitted to the Department of Gynecology and Oncology o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…For instance, Dermitzakis et al (2016) found that concurrent paclitaxel and carboplatin chemotherapy significantly influenced the PNS and SNS in ovarian cancer patients, predominantly affecting parasympathetic heart innervation. Liu et al (2023) showed that the combination of taxane and carboplatin chemotherapy could impact early ANS status in patients with cervical cancer. Meinardi et al (2001) discovered that even moderate doses of epirubicin were not associated with persistent alterations in HRV for breast cancer patients, suggesting a possible dose–response relationship for anthracycline-induced ANS damage.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Dermitzakis et al (2016) found that concurrent paclitaxel and carboplatin chemotherapy significantly influenced the PNS and SNS in ovarian cancer patients, predominantly affecting parasympathetic heart innervation. Liu et al (2023) showed that the combination of taxane and carboplatin chemotherapy could impact early ANS status in patients with cervical cancer. Meinardi et al (2001) discovered that even moderate doses of epirubicin were not associated with persistent alterations in HRV for breast cancer patients, suggesting a possible dose–response relationship for anthracycline-induced ANS damage.…”
Section: Discussionmentioning
confidence: 99%